Application Of Strategic Marketing On Tourism Management In Nigeria - Benson-Eluwa, Virginia (Archives of Business Research, 2019)
The work is on concepts of strategic thinking that are central to the efficient conduct of marketing-led organizations in travel and tourism. It stresses on the competitive future orientation of strategy in an era of globalization, constant change and the redrawing of traditional industry sector boundaries facilitated by information technology. Tourism growth is generally rapid although at varying degrees depending on the level of attention given, to the industry and technological advancement in the country.